2019
DOI: 10.1371/journal.pone.0223917
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium after lung resection for primary lung cancer: Risk factors, risk scoring system, and prognosis

Abstract: Delirium is a common post-surgical complication, but few studies have examined postoperative delirium following lung cancer surgery. The purpose of this study was to clarify the risk factors of postoperative delirium, to construct a useful scoring system, and to clarify the relationship between delirium and prognosis after lung cancer surgery. We retrospectively analyzed data from 570 patients who underwent surgery for primary lung cancer. Logistic regression analysis was used to determine the effects of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
13
3
1
Order By: Relevance
“…The incidence of delirium after thoracic surgery was reported to range from 5.3% to 6.7%, which was lower compared to that of our study [ 25 , 26 ]. This might be due to the retrospective nature of prior studies [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 89%
“…The incidence of delirium after thoracic surgery was reported to range from 5.3% to 6.7%, which was lower compared to that of our study [ 25 , 26 ]. This might be due to the retrospective nature of prior studies [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 89%
“…Hepatic and colorectal as well as lung cancer patients often developed delirium while delirium was less frequent in brain cancer patients. Studies on general ward and ICU patients who had undergone oncological surgery reported the following delirium frequencies: 7% for primary pulmonary malignancy [26], 8% for hepatocellular carcinoma [27], 7% for glioblastoma [28] and 14% for colorectal carcinoma [29]. Due to the exclusive inclusion of ICU patients, delirium was more frequent in the present study.…”
Section: Gouveia Et Al (N = 135contrasting
confidence: 38%
“…Comparing oncological patients with and without delirium, sepsis occurred in 26/176 (15%) and 6/312 (1.9%) patients (p < 0.001), while shock was diagnosed in 30/176 (6.1%) and 6/312 (1.9%) patients, respectively (p < 0.001). The SAPS II in delirious and non-delirious patients with malignancy was 41 (27-68) and 24 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), respectively (p < 0.001).…”
Section: Descriptive Datamentioning
confidence: 97%
“…In this case, it was also proven that despite the low frequency of delirium (6.7%), it significantly worsened the prognosis and overall survival. 32 Due to the presence of a factor specific to lung cancer surgery as one of the parameters, it is not possible to use it in other surgical fields.…”
Section: Discussionmentioning
confidence: 99%